Pengaruh Literasi Keuangan, Herding Behaviour, dan Financial Technology Terhadap Keputusan Investasi - Hariyanto, Bagas; Graciafernandy, Maria Agustine (Jurnal Ilmiah Aset, 2024)
The development of science and technology from time to time is very fast which requires individuals to be more able to follow developments to improve investment decisions on the Semarang University campus environment. The aim of this research is to analyze the influence of financial literacy, herding behavior and financial technology on investment decisions on the Semarang University campus environment. This research uses a random sampling method. The sample used in this research was 97 respondents from individuals on the Semarang University campus. Data analysis in this research used the SPSS version 25 program. Tests carried out included validity tests by comparing calculated r with r tables, reliability tests using Cronbach Alpha, classical assumption tests which included normality tests, multicollinearity tests, heteroscedasticity tests. Multiple analysis tests are used to test how much influence the independent variable has on the dependent variable and prove the research hypothesis, and also test the hypothesis with the t test, and test the coefficient of determination (R2). The results of this research provide the implication that financial literacy, herding behavior and financial technology are factors that need to be considered to improve individual investment decisions on the Semarang University campus environment.